The Role of Electronic Educational Language Games in Creating Good Learners - Hazaymeh, Omar (International Journal of Educational and Life Sciences, 2024)
The paper explores the electronic educational language games’ impact on learners’ development. As technology continues, electronic educational language games emerge as a promising tool to enhancing language acquisition skills and increasing academic performance. The paper reviews educational games’ literature to give understanding of the benefits of creating good learners and the associated challenges. The findings hope to give insights to optimize educational strategies in digital age, the discourse on technology’s role in enhancing learning outcomes and shaping the future of education. The findings suggest that such games have a role in having good learners, besides recommending that associated challenges require careful consideration. The paper ends with recommendations on harnessing the potential of these games to create good learners.